EFFECT OF THE USE OF HERBAL INGREDIENTS TO WEIGHT OF ABDOMINAL FAT AND VISCERAL ORGANS (LIVER, INTESTINE AND GIZZARD) IN BROILER - Poi, Hildegardis (Universitas Kanjuruhan Malang, 2015)
Research conducted at the laboratory Kanjuruhan University of Malang, On 25 march to 29 April 2014. Research objective is to determine the effect of the use of herbs to the weight of abdominal fat and visceral organs (liver, intestine and gizzard) in broiler chickens. The material used in this study were 80 head of DOC, cages, herbs (ginger, turmeric, ginger, garlic, betel leaf). The method used was completely randomized design (CRD) consisting of 4 treatments and 4 replications, each of which is P0 : without the addition of herbs, P1 : water + 10% herbal ingredients, P2 : water + 15% herbal ingredients, P0 : water + 20% herbal ingredients. Each experimental unit consisted of 5 chickens. Data were analyzed by analysis of variance followed by Least Significant Difference test (LSD).The results showed that administration of herbal ingredients into the drinking water of broiler chickens give effect was not significantly different(P>0.05) to the weight of abdominal fat, visceral organs (liver, intestine, gizzard). The results showed the amount of abdominal fatweightis the highest weight of P0: 25 g, and the lowest was P3: 17.5 g, analytical result obtained during the study of liver weight is the highest P0: the lowest is 8 2.5 g and P3: 62, 5 g, the highest weight of thei ntestine is P0: 60 g, and the lowest is P3: 50 g while the highest is P0 gizzard weight: 60 g, and the lowest is P3: 50 g.From the results of research into herbal drinking water in broiler chickens effect that was not significantly different (P> 0.05) to the weight of abdominal fat and viceral organs (liver, intestine, gizzard).Keyword: Herbal Ingredients, Abdominal Fat, Viceral Organ, Liver, Intestine, Gizzard, Broiler